An Analysis of Trading Activities, Contributions and Integration of Nigerian Traders in Ghana - Asante, K. (University Of Ghana, 2017)
This study examines the trading activities, contributions and integration of Nigerian traders in Ghana. The study explores more specifically, the study examines the migration processes, trading activities, livelihood strategies and integration of Nigerian traders in Ghana. The study employs the Push-pull and social network theories in explaining the factors responsible for the migration of Nigerian traders to Ghana. The study in general indicates that factors such as economic opportunities peace and stability in Ghana as well as the free movement ECOWAS Protocol were among the key determinants of their migration. However, they relied extensively on social networks in facilitating their migration to Ghana and these networks also supported them in their integration and adaptation process in Ghana. While their presence within the trading sector had increased competition between them and Ghanaians, the study also reveals various contribution been made by the traders in Ghana including the introduction of new ways of doing business. It also identifies the creation of employment opportunities where 69% had employed at least one Ghanaian in their businesses. Some had acquired properties such as houses, shops and commercial vehicles which serve to boost the economy and infrastructure in the country. The challenges facing the traders in Ghana include harassment at the borders and ports, agitation by Ghanaian traders, the recent power outages experienced in Ghana and the relatively high cost of living compared to Nigeria. Recommendations are therefore made to improve the provision of utility services especially electricity and the removal of the bottlenecks at the ports, borders and the acquisition of resident and work permit from the immigration office.
Thesis (M.A.)
Keywords: Trading Activities; Livelihood Strategies; Economic Opportunities; Migration; Ghana